Validity and Reliability Test of Indonesian Version B-IPQ to CRF Outpatients in RSUD Soedarso Pontianak - Nurul Hadisa; Ressi Susanti; Robiyanto Robiyanto (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Brief Illness Perception Questionnaire (B-IPQ) Instrument is a questionnaire to identify and assess the patient's perception of the disease, especially patients with chronic diseases. Chronic renal failure (CRF) is one of incurable diseases with the expensive cost of care and treatment. B-IPQ instrument has never been used yet in Indonesia to assess patients’ perceptions of chronic renal failure which have experience haemodialysis especially in Pontianak, West Kalimantan. The aim of this study was to determine the validity and reliability of B-IPQ instrument in Indonesian version on CRF patients at haemodialysis room RSUD Dokter Soedarso Pontianak. This study was a non-experimental study using cross-sectional method and prospective data collection. The sample is selected using non-probability sampling method rather purposive sampling technique, 30 CRF patients who had haemodialysis in November-December 2016 were taken as respondent. The validity test was conducted using Pearson correlation (correlation values ≥0.3) and reliability test using internal consistency (Cronbach alpha coefficient ≥0.7) technique. Validity test results showed a correlation value of each question was >0.3 (p: 0.05) and reliability test results showed Cronbach alpha coefficient was 0.755>0.7 (p: 0.05). The conclusion of this study was the B-IPQ instrument in Indonesian version is valid and reliable to measure the chronic renal failure patients’perception at haemodialysis room RSUD Dokter Soedarso Pontianak. Hence B-IPQ Indonesian version can be used directly to measure the perception of the disease in patients with CRF in order to help improve the quality of life of patients.